Fundação Therezinha Jansen: anteprojeto no imóvel da Rua Grande, nº 533 - Castro, Adriana Alice Sekeff (2009)
Draft revitalization of the property No 533, Rua Grande (Grand Street) in the historical core of São Luís of Maranhão, to adapt it to the Foundation Therezinha Jansen, to be created. The Jansen family is known in town for the past history and contributions in this, through the folk Terezinha Jansen (1928-2008). His home, where he lived throughout his life, the place is conducive to the creation of the cultural house that will house the Foundation will have its name. The building, which is in the toppling of State, remained in its restructuring with its main architectural features and restores the lost in order to expose another generation to the aesthetics of the houses of the historic city center. The Foundation will have a permanent exhibition on Therezinha Jansen and his family, and also will have workshops of folk dances she commanded. The project will contribute to the conservation, preservation and dissemination of cultural heritage Maranhão.